Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0091-001 International HVT/AC/198 GR/MLA 23rd May, 1939. Mr. George Reed, National Union of Seamen, St. George's Hall, Westminster Bridge Road, S.E.1. Dear Mr. Reed, SPANISH SEAMEN. Thank you for your letter of 22nd May, in which you enclose receipts in respect of payments to Spanish seamen for the period closing 13th May. I am attaching hereto cheque to the value of £390, and wish to take this opportunity of expressing to you and to the officers of your Union the Council's best thanks for making the arrangements for continuing the administration of these payments until we were in a position to secure the transfer of the work to the Trades Councils. Yours sincerely, Assistant Secretary. Cheque £390 292/946/25a/91